The effect of microteaching lesson study on the beliefs of EFL student teachers - Fitri Budi Suryani; Rismiyanto Rismiyanto (EduLite: Journal of English Education, Literature and Culture, 2021)
Microteaching lesson study, that is a variation of lesson study applied by student teachers in microteaching course, provides the environment for EFL student teachers to collaborate, engage, and reflect on their ideas, beliefs, and teaching experiences. Such condition is a fertile ground that enables the student teachers' beliefs of language learning to change. Recent studies show that some education programs have changed the beliefs of student teachers. However, no studies have discussed the changes of beliefs of English as a Foreign Language (EFL) student teachers experienced in microteaching lesson study. This present study aims to investigate the effect of microteaching lesson study on EFL student teachers’ beliefs. The data were collected using a questionnaire on Beliefs About Language Learning Inventory (BALLI) adapted from Horwitz administered before and after microteaching lesson study. The participants were the EFL student teachers enrolling in a microteaching lesson study class at Universitas Muria Kudus. The study reveals that the beliefs of EFL student teachers did not change significantly after they experienced microteaching lesson study. Time seems to be one of the most influential factors in hindering the changes of beliefs of the EFL student teachers. Therefore, this study suggests that EFL student teachers be given more time to practise teaching in the microteaching course.